Effects of different cutting methods and additives on the fermentation quality and microbial community of Saccharum arundinaceum silage - Zheng, Yulong; Li, Mengxin; Xu, Jinyi; Sun, Hong; Cheng, Qiming; Xie, Yixiao; Wang, Chunmei; Chen, Chao; Li, Ping (Frontiers in Microbiology, 2022)
To develop a new high-yielding and polysaccharide-containing forage resource for livestock, the effects of different cutting methods and additives on Saccharum arundinaceum silage were evaluated. The wilted S. arundinaceum were chopped and knead-wired. The silages from each cutting method were treated with Lactobacillus plantarum (LP), cellulase (CE) and the combination of LP and CE (LP+CE) for 3, 7, 15, 30 and 60 days. Compared with the CK treatment, CE treatment exhibited better effects in the degradation of neutral detergent fibre (NDF), LP exhibited a better performance in preserving the content of dry matter (DM), and adding LP+CE significantly enhanced (P<0.05) the contents of lactic acid (LA), crude protein (CP) and DM and significantly reduced (P<0.05) the pH and NDF content during ensiling. In addition, both additives exerted a remarkable effect on the silage bacterial community (P<0.05), with a dramatic increase in the Lactobacillus abundance and a decrease in the abundance of Enterobacter. Lactic acid bacteria (LAB) became the most dominant bacteria that affected the fermentation quality of LP and LP+CE silages. Meanwhile, chopped silages showed better fermentation quality and nutrient preservation and a higher abundance of LAB. Our research indicated that the chopped S. arundinaceum ensiling with LP+CE could exert a positive effect on LA fermentation and preservation of nutrient substances by shifting the bacterial community. In conclusion, S. arundinaceum can serve as a new silage resource for feed utilization by the ensiling method of LP+CE-chopped.